Cavity Preparation by Laser in Primary Teeth: Effect of 2 Levels of Energy Output on the Shear Bond Strength of Composite Restoration to Dentin - Paryab, Mehrsa; Sharifi, Shahrzad; Afshar, Hossein; Kiomarsi, Nazanin; Kharazifard, Mohammad javad (Journal of Lasers in Medical Sciences, 2019)
Introduction: One of the main applications of laser in dentistry is the removal of dental caries and preparation of restorative cavities. The morphology and wettability of laser prepared surfaces are different from that of those prepared with conventional method which may affect the quality of the adhesive potential of bonding agents in these surfaces. This study aimed to assess the shear bond strength of a total-etch and self-etch adhesive system to primary tooth dentin prepared by two different energy densities of Er:YAG laser in comparison with surfaces prepared by bur. Methods: A total of 60 human primary second molars extracted for orthodontic purposes were selected and randomly divided into 3 main groups of equal (n = 20). Group A: Preparation of dentin surface by bur; group B: Preparation of dentin surface by laser with 300 mJ energy level; group C: Preparation of dentin surface by laser with 400 mJ energy level. In each of the main groups, the teeth were randomly assigned to 2 subgroups. Composite resin material was bonded with the total-etch adhesive system in subgroups A1, B1, and C1 and with the self-etch adhesive system in subgroups A2, B2, and C2. The samples were thermo-cycled, and composite restorations shear bond strength was measured in MPa. Data were analyzed using two-way analysis of variance (ANOVA), and P values less than 0.05 were considered statistically significant. Results: The highest and the lowest shear bond strength values were observed in group A2 (Preparation by bur- Composite resin material bonded by Clearfil SE Bond) and group C2 (Preparation by laser with 400 mJ energy level - Composite resin material bonded by Clearfil SE Bond), respectively. The results showed no statistically significant differences between the study subgroups (P > 0.05). Conclusion: It is concluded that in terms of shear bond strength to dentin, Single Bond and Clearfil SE Bond adhesive agents adequately perform in primary tooth dentin prepared by Er: YAG laser with energy levels of 300 and 400 mJ and frequency of 10 Hz.